2019
DOI: 10.1177/0047287519880000
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Travelers’ Psychological Distance, Language Abstraction, and Message Appeal Type in Social Media Advertising

Abstract: Effectiveness of destination advertising to potential tourists has been enhanced with the use of personalized orientation. After an online search for information about a destination, individuals are exposed to advertisements related to the destination on their social media newsfeed. However, further understanding is warranted in terms of how these destination messages should be crafted. Thus, our research aims to uncover how destination advertising design, message appeal type, and language abstraction level in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 44 publications
4
53
0
Order By: Relevance
“…(2) the measurement of engagement with DMOs/NTOs' SNSs [9,21]; (3) the analysis of the drivers of travelers' engagement with and contribution to DMOs/NTOs' SNSs [42,43]; (4) new methodologies to measure travelers' attitudes towards destinations and attractions by means of SNSs' content analysis [20,22,30,44]; (5) tourists' destination experiences with DMOs' SNSs [45][46][47][48][49]; and (6) the impact of DMOs' SNSs on online travelers' attitudes, visit and recommendation intentions, reactions to marketing and advertising messages, and bookings [29,31,33,[50][51][52][53][54][55][56][57][58]. Overall, and regardless of the topic covered, there is a prevalence of studies on Facebook (31 studies), Twitter (21 studies), YouTube (15 studies) and TripAdvisor (10 studies).…”
Section: Level Of Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…(2) the measurement of engagement with DMOs/NTOs' SNSs [9,21]; (3) the analysis of the drivers of travelers' engagement with and contribution to DMOs/NTOs' SNSs [42,43]; (4) new methodologies to measure travelers' attitudes towards destinations and attractions by means of SNSs' content analysis [20,22,30,44]; (5) tourists' destination experiences with DMOs' SNSs [45][46][47][48][49]; and (6) the impact of DMOs' SNSs on online travelers' attitudes, visit and recommendation intentions, reactions to marketing and advertising messages, and bookings [29,31,33,[50][51][52][53][54][55][56][57][58]. Overall, and regardless of the topic covered, there is a prevalence of studies on Facebook (31 studies), Twitter (21 studies), YouTube (15 studies) and TripAdvisor (10 studies).…”
Section: Level Of Analysismentioning
confidence: 99%
“…The drivers of adoption and acceptance of Web 2.0 technologies by DMOs and destination marketers have been examined in relation to several factors: the opportunities and costs of developing SNSs [19,56,[64][65][66]; the budget, resources and time constraints [9,36,49,67,68]; the skills, knowledge, experience and competences needed to deploy Web 2.0 technologies professionally [23,69]; the social capital and trust requirements [35]; the need to develop and nurture a virtual community [70]; and the connectivity to other ICT websites [58].…”
Section: Drivers Of Adoption and Acceptance Of Web 20 Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In today’s online market where review platforms must compete constantly with existing platforms and newcomers, the findings in this study provide useful practical implications for platform developers, marketers, and tourists. Previous studies have shown that the appeal of social media advertisements depends on a diversity factors that are attributable to both platform and tourists (Wang and Lehto 2019). First, the findings suggest that the effects of expert power depend on the power of users.…”
Section: Discussionmentioning
confidence: 99%